Iron Particles Enhance Visualization of Experimental Gliomas with High-Resolution Sonography - Nolte, Ingo (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: Intraoperative MR imaging and sonography are used for navigation during neurosurgical procedures. The purpose of this experimental study was to evaluate the potential of high-resolution sonography using superparamagnetic iron oxide (SPIO) particles as a contrast medium to delineate brain tumors and to relate these findings with those of MR imaging. METHODS: C6 gliomas were implanted in 36 rats. Eleven days after tumor implantation, the animals underwent MR imaging with a 1.5-T MR imaging unit. Twelve animals received gadopentetate dimeglumine immediately before the MR examination, 12 animals were injected with SPIO particles 24 hours before MR imaging, and 12 animals received no contrast agent. Immediately after MR imaging, the animals were sacrificed and their brains were removed and placed in saline. Sonography was performed instantly after brain removal. Brains were embedded in paraffin, and sections were stained for iron with Perl’s stain and for macrophages with ED-1 immunohistochemistry. RESULTS: At MR imaging, the tumors appeared hyperintense on T2-weighted and gadolinium-enhanced T1-weighted images. After application of SPIO particles, they became markedly hypointense on T2-weighted images and hypo- to hyperintense on T1-weighted images. On sonograms, gliomas were iso- to slightly hyperechoic to normal brain parenchyma on nonenhanced and on gadolinium-enhanced images. After application of SPIO particles, tumors became markedly hyperechoic and were distinctly demarcated from the surrounding brain tissue. CONCLUSION: SPIO particles improved the detection and demarcation of the experimental gliomas on sonograms, which may improve intraoperative neuronavigation with sonography.